Hepatitis E risks: pigs or blood—that is the question. Issue 2 (February 2017) - Tedder, Richard S.; Ijaz, Samreen; Kitchen, Alan; Ushiro‐Lumb, Ines; Tettmar, Kate I.; Hewitt, Patricia; Andrews, Nick
Abstract : BACKGROUND: Infection with hepatitis E virus (HEV) Genotype 3 is recognized as a food‐borne zoonosis in developed countries where it usually causes a mild self‐limited acute hepatitis. It may cause a persistent infection in the immunosuppressed human that can progress to cirrhosis. To protect the patient from transfusion‐acquired HEV infection, steps have been taken in the United Kingdom to provide for at‐risk patients only components from donors screened for HEV viremia. This strategy does not protect from dietary exposure and calls into question estimation of relative risk between blood transfusion and diet. STUDY DESIGN AND METHODS: Using data on HEV viremia, component exposure, residual plasma volume, and resulting transmission, the dose of virus administered and subsequent transmission rates were determined and used to populate a model that can infer the relationship between blood and dietary exposure. RESULTS: The annual attack rate of a population, defined as seroconversion, provides an estimate of the risk of receiving a component containing HEV from a viremic donor. The lowest viral dose that resulted in infection was 2 × 10 4 IUs and 55% of components containing this dose transmitted infection. The transfusion risk of infection only exceeds the annual dietary risk when more than 13 individual donor components are transfused. CONCLUSION: For many solid organ transplant patients dietary exposure far exceeds the risk of transfusion from unscreened donors. It is only in the immunosuppressed patient requiring extensive blood component support that transfusion risk dominates. This understanding should inform policy decisions on HEV RNA screening of blood donations.